Respuesta :

Answer:

y = -3x - 3

Step-by-step explanation:

First, determine the slope of the red line.  As we move from (0, 3) to (1, 0),

x increases by 1 and y decreases by 3.  Hence, the slope, m, is

m = rise / run = -3 / 1, or m = -3.

The desired new line, parallel to the red line, has the same slope as the red line:  m = -3.

The equation for this new line is y - k = m (x - h), where (h, k):  (-1, 0):

We get y - 0 = -3 (x + 1), or y = -3x - 3.

Check:  Does this line go thru the given point (-1, 0)?

Is 0 = -3(-1) - 3 true?  Yes, it is true.